2019
DOI: 10.1186/s12889-019-7547-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of trends in neonatal, post-neonatal, infant, child and under-five mortalities in Tanzania from 2004 to 2016

Abstract: Background Under-five mortality is still a major health issue in many developing countries like Tanzania. To achieve the Sustainable Development Goal target of ending preventable child deaths in Tanzania, a detailed understanding of the risk factors for under-five deaths is essential to guide targeted interventions. This study aimed to investigate trends and determinants of neonatal, post-neonatal, infant, child and under-five mortalities in Tanzania from 2004 to 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
74
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 51 publications
18
74
5
Order By: Relevance
“…Study factors were selected based on past studies from LMICs [14,33,34,40,41] and data availability in the TDHS. These factors were broadly classified into predisposing, enabling, need and community-level factors based on the conceptual model of health services utilization, proposed by Andersen to explain the conditions that favour or hinder an individual from seeking health care [42].…”
Section: Study Factors Influencing the Utilization Of Ancmentioning
confidence: 99%
See 1 more Smart Citation
“…Study factors were selected based on past studies from LMICs [14,33,34,40,41] and data availability in the TDHS. These factors were broadly classified into predisposing, enabling, need and community-level factors based on the conceptual model of health services utilization, proposed by Andersen to explain the conditions that favour or hinder an individual from seeking health care [42].…”
Section: Study Factors Influencing the Utilization Of Ancmentioning
confidence: 99%
“…Although Tanzania was one of the countries that achieved a key target of the Millennium Development Goals (MDG-4, to reduce child mortality) [13,14], recent evidence from the country has indicated that 8200 maternal deaths occurred in 2015 [7]. This suggests that MDG-5 (to improve maternal health) still needs significant attention in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information on the survey methodology is provided in the final NDHS reports [24][25][26][27][28]. In the present study, a total weighted sample of 103,903 most recent live-birth children under 5 years of age was used to minimize the potential effect of recall bias, consistent with Measure DHS approach [24] and used in previously published studies [29][30][31][32].…”
Section: Data Sourcesmentioning
confidence: 99%
“…The NDHS categorized household wealth index into five quintiles (poorest, poorer, poor, rich, or richest). In this study, the household wealth index was reclassified as 'poor', 'middle', or 'rich', to increase the sample within each category, consistent with past studies [31,37,38]. Media exposure included frequency of reading magazines or newspapers, frequency of listening to the radio, and frequency of watching TV, which were grouped as 'Yes' or 'No'.…”
Section: Study Variablesmentioning
confidence: 99%
“…In Tanzania, the probability of children under five dying before celebrating their fifth birthday is 53 deaths per 1000 live births. While neonatal mortality remained unchanged, Tanzania had seen a fall in the burden of post neonatal mortality rates, child mortality rates, infant mortality and under-five mortality rates [25]. Individuals aged 15 to 60 have a probability of dying of 299 and 222 deaths per 1000 population respectively.…”
Section: Brief Overview Of the Study Settingmentioning
confidence: 99%